Evaluasi Stategi Penerapan Harga dalam Menghadapi Kompetisi (Studi Kasus pada RSIA ABC) - Fikri, Dzar Ikramul; Hilda Rossieta (Owner : Riset dan Jurnal Akuntansi, 2024)
Mother and child hospitals must have a competitive strategy in pricing to face competition because of the limited acceptance of patient services that are outside their specialty patients. On the basis of this competitive strategy, RSIA can create a pricing strategy to be able to take the existing market share. This study aims to evaluate pricing strategies with criteria for factors in setting prices, namely management strategies in dealing with competitors, customer interest, and costs. This research was conducted with an evaluation-based case study method and descriptive qualitative to describe the understanding related to the situation of the object of research carried out with the natural conditions of the object of research. The research was conducted by collecting data by interview, questionnaire and document. The object of this research is RSIA ABC with a pricing strategy for inpatient delivery in 2022. The results of this study are the inaccuracy of the pricing strategy by RSIA ABC where RSIA ABC uses the best cost provider in facing competitors but the prices offered tend to be expensive in normal labor services and competitive in SC / Caesarean delivery. The service features offered by RSIA ABC are also less in quantity than competitors. Patient opinions also corroborate the existence of errors in the strategy of applying prices and the mismatch of understanding the value of service features set by management as a competitive advantage by customers is considered not so important. In terms of cost calculation, RSIA ABC also does not calculate costs accurately and some costs are based on market analysis only. Therefore RSIA ABC must increase service features that are unique to RSIA ABC in quantity and customer assessment, as well as more accurate cost calculations based on an understanding of cost accounting.